Intersectional Feminism in the Selected Poems from the Jim Crow, Harlem Renaissance, and Contemporary Era by African-American Female Poets - Nur Azizah (Lakon : Jurnal Kajian Sastra dan Budaya, 2024)
This study aims to analyze the theme of intersectional in poetry written during three important periods: the Jim Crow Era, Harlem Renaissance, and Contemporary Era. Using close reading, this research explores how racism, sexism, and social class are intertwined and reflected in the works of poets, particularly women of color. The analysis is conducted by paying attention to the use of diction, symbolism, and poetic structure, as well as the social and historical context in which the poems were written. The results show that intersectional is a central element that shapes the experience of oppression in poetry from each era. In the Jim Crow Era, poets express racial and gender violence through strong and straightforward language, emphasizing the brutal reality of segregation and misogyny. In the Harlem Renaissance, there is an attempt to celebrate cultural identity while still considering the complexities of gendered oppression, with poets combining pride in Black identity with critiques of patriarchy. In the Contemporary Era, the complexities of intersectional identities are increasingly explored, reflecting the challenges faced by women of color in modern society, including issues of sexuality, queerness, and class dynamics. This research confirms that despite advances in social awareness, issues of racism and gender oppression remain enduring legacies, with poetry serving as both a reflection of these struggles and a form of resistance against them. Through this exploration, the study underscores the vital role of intersectional feminism in understanding the evolving experiences of African American women across time.